Perluasan Theory of Planned Behavior: Peran Authenticity dan Trustworthiness - Devani Sephia Dewi; Adhi Prakosa; Guruh Ghifar Zalzalah (Pusat Riset dan Inovasi Nasional, 2026)
The food and beverage industry in Indonesia is growing rapidly through digital marketing, particularly through the role of influencers in influencing consumer preferences and purchase intentions. Several influencers are no longer merely collaborating with brands, but are also becoming business owners by leveraging their personal branding and follower base. However, when promoting their own products, the effectiveness of these strategies on purchase intentions is not always consistent. This study aims to examine the influence of the Theory of Planned Behaviour on purchase intention and analyse the role of Parasocial Relationship through influencer authenticity and influencer trustworthiness in regional cuisine at RM Padang Payakumbuah. The research uses a quantitative approach with data from 182 respondents in the Special Region of Yogyakarta, analysed using PLS-SEM. The results show that attitude and influencer authenticity do not have a significant effect on purchase intention, while subjective norm and perceived behavioural control have a significant effect. Furthermore, influencer trustworthiness strengthens the relationship between perceived behavioural control and purchase intention. These findings emphasise the importance of social recommendations, ease of purchase access, and building trust towards influencers.